Climate change and freshwater availability: present and future challenges / Izzadin Ali, Dasimah Omar and Siti Mazwin Kamaruddin - Ali, Izzadin; Omar, Dasimah; Kamaruddin, Siti Mazwin (Penerbit UiTM (UiTM Press), 2016)
The interrelationship between freshwater availability with the growing population and climate change estimates is complex. This article investigates climate change role in freshwater resources availability. This is critical issue as freshwater is vital resource for life, and it is in stake as it is depleted worldwide. Intergovernmental Panel on Climate Change (IPCC) Special Report on Emissions Scenarios (SRES) was discussed. This paper elucidates the climate model downscaling methods used by scholars for future projections. The applications of modelling could provide a holistic approach based on historical data to predict the effect of climate change on the availability of freshwater. However, the people variability uncertainties dominate assessments of freshwater stress, whilst climate change projections uncertainties are more hypothesized to play a smaller role than people.